Mood booster / Abdul Jalil Mohammad Ali...[et al.] - Mohammad Ali, Abdul Jalil; Ahmad Razif, Muhammad Hariz; Saidan, Muhammad Syazwan; Redzuan, Muhammad Syafiq; Mohamed Saphi, Mohamad Shafiq; Shadan, Mohamad Najib; Abd. Hamid, Aiedeel Ikhmal (2018)
Everyday life can no longer be imagined without fragrances and scented products. Humans have tempted to have perfumes or fragrances, which emulates nature's pleasant smells. Perfumes today are being made and used in different ways than in previous centuries. Perfumes are being manufactured more and more frequently with synthetic chemicals rather than natural oils. Less concentrated forms of perfume are also becoming increasingly popular. Combined, these factors decrease the cost of the scents, encouraging more widespread and frequent, often daily use. Using perfumes to heal, make people feel good and improve relationships between the sexes are the new frontiers being explored by the industry. The sense of smell is considered a right brain activity which rules emotions, memory, and creativity. The smelling oils and fragrances to cure physical and emotional problems is called aromatherapy can help to balance hormonal and body energy. The theory behind aromatherapy states that using essential oils helps bolster the immune system when inhaled or applied topically. Smelling sweet smells also affects one's mood and can be used as a form of psychotherapy. Thus, a new technology must be applied to make home fragrance a much more efficient use by having as many type of perfume you can store and at the same time you can mix it up to decide which smell suits the environment. Therefore, our company, MEWANGI Enterprise has introduced a product which is Mood Booster which the fragrance can be controlled by the tip of our finger.